2019
DOI: 10.1007/s12264-019-00395-4
|View full text |Cite
|
Sign up to set email alerts
|

Poly-PR in C9ORF72-Related Amyotrophic Lateral Sclerosis/Frontotemporal Dementia Causes Neurotoxicity by Clathrin-Dependent Endocytosis

Abstract: GGGGCC repeat expansions in the C9ORF72 gene are the most common cause of amyotrophic lateral sclerosis and frontotemporal dementia (c9ALS/FTD). It has been reported that hexanucleotide repeat expansions in C9ORF72 produce five dipeptide repeat (DPR) proteins by an unconventional repeat-associated non-ATG (RAN) translation. Within the five DPR proteins, poly-PR and poly-GR that contain arginine are more toxic than the other DPRs (poly-GA, poly-GP, and poly-PA). Here, we demonstrated that poly-PR peptides trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 75 publications
2
18
2
Order By: Relevance
“…S10C ). In contrast to our data, a previous study showed that treatment of a high dose (10 μmol/L) of PR 20 in SH-SY5Y cells led to increased level of p53, albeit with a significant amount of cell death ( 63 ). Thus, further studies are required for understanding a potential role of p53 in mediating PR-induced Fibrillarin induction.…”
Section: Discussioncontrasting
confidence: 99%
“…S10C ). In contrast to our data, a previous study showed that treatment of a high dose (10 μmol/L) of PR 20 in SH-SY5Y cells led to increased level of p53, albeit with a significant amount of cell death ( 63 ). Thus, further studies are required for understanding a potential role of p53 in mediating PR-induced Fibrillarin induction.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on this study, we speculate that in C4 da neurons expressing V5-PR36, heterozygous stau mutation may have decreased p53 level, with subsequent increased Fibrillarin production. In contrast to our speculation, a previous study showed that treatment of a high dose (10μmol/L) of PR 20 in SH-SY5Y cells led to increased level of p53, albeit with a significant amount of cell death [38]. Thus, further studies are required for a potential role of p53 in mediating Staufen-dependent PR toxicity.…”
Section: Discussioncontrasting
confidence: 97%
“…This in itself is reported to upregulate RAN translation, driving further production of DPRs and becoming a feed-forward loop (Zhang et al, 2014 ). In a different study, expression of synthetic poly(PR) induced ER stress and inhibition of the UPR increased cell survival (Wang et al, 2019 ). Consistent with these reports, RAN translation of the G 4 C 2 expansion was also found to be enhanced by ER stress and overexpression of the repeats impaired global translation, while increasing the formation of stress granules in an eIF2α-dependent manner (Green et al, 2017 ).…”
Section: Upr Activation In Alsmentioning
confidence: 99%